2007
DOI: 10.1111/j.1600-0536.2007.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of barrier creams – introduction and comparison of 3 in vivo methods

Abstract: Often barrier creams (BC) do not fulfil their protecting behaviour, even when promised by the manufacturers. Therefore, it is of great importance to develop standardized in vivo techniques to prove the potency of BC in humans. In the present study, 3 promising techniques for the analysis of BC were evaluated: laser scanning microscopy, laser doppler flowmetry, and the tape-stripping procedure. Sodium fluorescein and glycerol trinitrate acted as hydrophilic model-penetrating substances. By means of these method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…Hence, a comparison between products and the known effects of skin protection reference samples is made possible, thus establishing a quality standard. The dose applied in the model was approximately 3 mg/cm 2 – according to recent findings on the amount of skin protection products required under working conditions – and thus was lower than in the majority of experimental studies published to date . By establishing uniform in vivo test standards, the prerequisites for product comparability and improved market transparency for users of skin protection products were thus to be created.…”
Section: Skin Products In Primary and Secondary Prevention Of Occupatmentioning
confidence: 99%
“…Hence, a comparison between products and the known effects of skin protection reference samples is made possible, thus establishing a quality standard. The dose applied in the model was approximately 3 mg/cm 2 – according to recent findings on the amount of skin protection products required under working conditions – and thus was lower than in the majority of experimental studies published to date . By establishing uniform in vivo test standards, the prerequisites for product comparability and improved market transparency for users of skin protection products were thus to be created.…”
Section: Skin Products In Primary and Secondary Prevention Of Occupatmentioning
confidence: 99%
“…The assessment methods often consist of clinical scoring of irritation after cutaneous patch tests (n = 17) and bioengineering methods which are habitually evaporimetry (n = 17), colorimetry (n = 12), corneometry (n = 7), flow velocimetry by Doppler laser (n = 6), spectrometry (n = 3) or other more infrequently used methods. Two studies showed an increased penetration of the irritant [27,45], and the irritation increased in 3 trials [26,32,50]. Table 2 displays the protective effects of the 4 most used BCs.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 39 controlled trials (table 1) investigating the effect of BCs against skin irritants in a total of 929 volunteers (172 men, 279 women and 481 unspecified subjects) with healthy skin (n = 28), hand dermatitis (n = 1), skin sensitized to a specific allergen (n = 4) and 1 study on latex glove allergens [6,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52]. From these 39 papers, studies on excised skin [18,24,40,41,43,46] have been discarded, and only trials on subjects with healthy and non-sensitized skin were retained, reducing the list to 27 papers detailed in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Ein Vergleich zwischen Produkten und den bekannten Wirksamkeiten der Hautschutzreferenzmuster wird dadurch ermöglicht und dadurch ein Qualitätsmaßstab etabliert. Die im Modell applizierte Dosis wurde mit 3 mg/cm 2 – nach neueren Erkenntnissen zur Auftragsmenge von Hautschutzprodukten unter Arbeitsbedingungen – angenähert und lag damit niedriger als in der Mehrzahl der bisher publizierten experimentellen Studien . Durch Schaffung von einheitlichen In‐vivo‐Prüfstandards sollten damit die Voraussetzungen einer Produktvergleichbarkeit und verbesserten Markttransparenz für Anwender von Hautschutzprodukten geschaffen werden.…”
Section: Hautmittel In Der Primären Und Sekundären Prävention Berufsbunclassified